Effects of Dietary Inclusion of Chlorella vulgaris on Growth, Blood Biochemical Parameters, and Antioxidant Enzyme Activity in Olive Flounder, Paralichthys olivaceus. Issue 1 (3rd June 2016) - Rahimnejad, Samad; Lee, Sang‐Min; Park, Heum‐Gi; Choi, Jin
Abstract: This study was carried out to investigate the effects of dietary inclusion of defatted Chlorella on growth performance, body composition, blood biochemistry, and antioxidant enzyme activity in olive flounder. Four isonitrogenous (51% crude protein) diets were formulated to contain 0 (control), 5, 10, or 15% Chlorella meal (CM) (designated as Con, CM5, CM10, and CM15, respectively) and fed to triplicate groups of fish (104.4 g) to apparent satiation twice daily for 8 wk. At the end of the feeding trial, significant enhancement ( P < 0.05) in growth performance was obtained at over 10% CM compared to fish fed the control diet. No significant changes in dorsal muscle and liver proximate composition were found following CM administration. The groups fed CM‐containing diets revealed significantly lower plasma cholesterol concentration than those fed the control diet. Dietary CM affected antioxidant enzyme activity; significantly higher plasma catalase activity was found in fish fed ≥10% CM and total antioxidant capacity increased in CM5 and CM10 groups compared to the control. However, plasma glutathione peroxidase and superoxide dismutase activities were not significantly influenced by dietary CM. Also, significant enhancement in 1, 1‐diphenyl‐2‐picryl‐hydrazyl radical scavenging activity was found in dorsal muscle of fish fed CM15 diet compared to the control. The findings in this study showed that dietary inclusion of 10–15% CM can enhance growth performance and affect antioxidant enzyme activity and lipid metabolism in olive flounder.